Characterizing cellular membrane partitioning of DMSO using low-temperature Raman spectroscopy - Louwagie, Troy; Wagner, Madeline; Li, Rui; Yu, Guanglin; Petersen, Ashley; Hubel, Allison (Frontiers in Molecular Biosciences, 2023)
Additives that help cells survive the stresses of freezing and thawing are known as cryoprotective3 agents (CPAs). Two different types of CPAs have been identified: penetrating and non-penetrating. Common penetrating CPAs include dimethylsulfoxide (DMSO) and glycerol. The location of a CPA (intracelluar or extracellular) is important for understanding the molecular mechanisms of action for the solution. Low Temperature Raman spectroscopy is a label-free method of detecting the location of CPAs at low temperature with high spatial resolution and chemical specificity. To this end, cells cryopreserved in DMSO using a variety of cooling rates and DMSO concentrations and imaged using Raman spectroscopy were analyzed using automated image analysis to determine the partitioning ratio (Concentration of DMSO outside/concentration of DMSO inside the cell). The partitioning ratio was roughly 1 for T-cells frozen at 1 ◦C/min in varying concentrations of DMSO with the exception of 1% DMSO which had a partitioning ratio of 0.2. The partitioning ratio increased from 1 to 1.3 as the cooling rate increased from 1 to 5 ◦C/min. Different cell types exhibited differences in partitioning ratio when frozen in 10% DMSO and 1 ◦C/min suggesting that differences in freezing response may result from differences in solute partitioning. The presence of intracellular ice resulted changed the distribution of DMSO inside the cell and also the partitioning ratio.